MONITORING THE STATUS OF A SMART HOME USING IOT TECHNOLOGY - Otrokh, S. I.; Kublii, L. I.; Zashchytynska, M. O. (Systems and Technologies, 2026)
The article provides a detailed analysis of the process of developing a smart home monitoring system model based on Internet of Things (IoT) technologies and reveals the key aspects of building modern intelligent home automation systems. It examines the conceptual principles of smart home operation, which involve close interaction between sensors, microcontrollers, gateways, and actuators in real time. It is the combination of these components that enables the continuous collection, analysis and processing of data necessary to control environmental parameters and improve the safety, comfort and energy efficiency of residential premises. The paper conducts a thorough study of the architecture of the IoT system and describes the principles of its implementation in the Cisco Packet Tracer virtual environment, which serves as a tool for modelling the interaction of IoT devices without the need for physical equipment. Particular attention is paid to algorithms for automatic response to events. This approach demonstrates the importance of integrating intelligent control mechanisms that form the basis of the concept of a ‘smart’ living environment. The technical and functional capabilities of the developed model are considered separately. The characteristics of the types of sensors used, methods of data transmission, features of component interaction within a local network, as well as means of ensur- ing the stability and correct operation of the system are presented. The model was tested, and the results confirmed its reliability, the coordination of individual IoT components, and the system’s ability to perform basic security monitoring functions in automatic mode. The results obtained indicate the feasibility of using the created model as a training tool for acquiring practical skills in the field of IoT technologies, as well as a demonstration example for studying the principles of building integrated smart home systems. The article demonstrates an approach to creating IoT solutions focused on ensuring user safety and comfort. The devel- oped model can serve as a basis for further experiments and research in the field of residential automation and is a relevant example of the application of Internet of Things technologies in the current conditions of digital infrastructure development.